The Epistemic Division of Labor Revisited. - Thoma, Johanna (Philosophy of Science, 2015)
Some scientists are happy to follow in the footsteps of others; some like to explore novel approaches. It is tempting to think that herein lies an epistemic division of labor conducive to overall scientific progress: the latter point the way to fruitful areas of research, and the former more fully explore those areas. Weisberg and Muldoon's model, however, suggests that it would be best if all scientists explored novel approaches. I argue that this is due to implausible modeling choices, and I present an alternative 'epistemic landscape' model that demonstrates the alleged benefits from division of labor, with one restriction.